New Phase Transition Related to the Black Hole's Topological Charge. (2nd January 2019) - Lan, Shan-Quan; Li, Gu-Qiang; Mo, Jie-Xiong; Xu, Xiao-Bao
Abstract : The topological chargeϵ of AdS black hole is introduced by Tian et al. in their papers, where a complete thermodynamic first law is obtained. In this paper, we investigate a new phase transition related to the topological charge in Einstein-Maxwell theory. Firstly, we derive the explicit solutions corresponding to the divergence of specific heatC ϵ and determine the phase transition critical point. Secondly, theT - r curve andT - S curve are investigated and they exhibit an interesting van der Waals system's behavior. Critical physical quantities are also obtained which are consistent with those derived from the specific heat analysis. Thirdly, a van der Waals system's swallow tail behavior is observed whenϵ > ϵ c in theF - T graph. What is more, the analytic phase transition coexistence lines are obtained by using the Maxwell equal area law and free energy analysis, the results of which are consistent with each other.